BENARKAH INOVASI MEMPENGARUHI KINERJA UMKM? (STUDI KASUS DI GRESIK DAN SIDOARJO) - Florencia Irena; Lusy Lusy (ITB AAS Indonesia Surakarta, 2023)
The aims of this study is examining the effect of Financial Literacy, Dynamic Capabilities, Marketing Communication on Firm Performance, especially MSMEs in Gresik and Sidoarjo with Innovation as a mediating variable. This study used quantitative analysis by distributing questionnaires to 100 MSMEs in Gresik and Sidoarjo Regencies. This research was processed using Structural Equation Modeling (SEM) analysis using SmartPLS. The results of this study indicate that Financial Literacy and Marketing Communication have an effect on Innovation. However, Innovation is not influenced by Dynamic Capabilities. The dynamic ability of MSME actors does not always guarantee the creation of Innovation. Moreover, Innovation does not mediate Dynamic Capabilities on Firm Performance. This reflects that business actors have other ways to analyze and improve the Firm Performance. These results show that Innovation mediates Financial Literacy, MSME actors who carry out Financial Literacy understand that Innovation is needed in the business world. In addition, Innovation mediates Marketing Communication to Firm Performance, because MSME actors understand the importance of Innovation in conducting marketing communications.